Environmental assessment of the use of emulsion explosives in underground iron ore mining - Khomenko, O.; Kononenko, M.; Myronova, I.; Kosenko, A.; Cabana, Edgar Cáceres (My University, 2024)
The article provides a comprehensive analysis of using TNT-free explosives (E) in the iron ore mining sector in Ukraine. It delves into the development and application of a specific type of emulsion explosive known as "Ukrainit," which is free from TNT, with the objective of its adoption in underground iron ore mining operations. Pilot blasting activities were carried out at PJSC "Zaporizhzhia Iron Ore Plant" (PJSC "ZIOP"), selected for its state-of-the-art equipment and advanced ore extraction technology. Through examination of ground-level concentrations of environmentally hazardous substances, the study revealed that the highest levels of carbon monoxide, nitrogen oxide, and dioxide were observed in 2008 when underground mining operations exclusively used 100% TNT-containing E. However, by the year 2020, a situation changed with implementation of a blend comprising 78% "Ukrainit" type EE and 22% TNT-containing explosives, resulting in a notable decrease in the maximum concentrations of environmentally hazardous substances compared to 2008. Specifically, carbon monoxide level decreased by 5.0–5.5 times, while nitrogen oxide and dioxide levels decreased by 1.2–1.3 times. Furthermore, use of "Ukrainit" type EE at PJSC "ZIOP" led to a 1.5 times decrease in the environmental hazard index on average (reduced to 36%) compared to the usage of TNT-containing E. These findings underscore the significant environmental benefits associated with the adoption of TNT-free explosives in iron ore mining operations, particularly in mitigating the release of harmful substances and reducing environmental risks.
Keywords: emission source; ground concentration; environmentally hazardous substances; emulsion explosives; environmental hazard index; environmental assessment